Practitioner Review: Social (pragmatic) communication disorder conceptualization, evidence and clinical implications. (9th October 2013) - Norbury, Courtenay F.
<x xml:space="preserve">Abstract</x> Background DSM‐5 sees the introduction of Social (Pragmatic) Communication Disorder (SPCD), characterized by persistent difficulties using verbal and nonverbal communication for social purposes, in the absence of restricted and repetitive interests and behaviours. There is currently much confusion about the precise diagnostic criteria for SPCD and how this disorder relates to autism spectrum disorders (ASD), previous descriptions of pragmatic language impairment (PLI) and more specific language disorders (LD). Method Proposed criteria for SPCD are outlined. A selective review of the evidence considers whether these criteria form a cohesive and distinct diagnostic entity. Approaches to assessment and intervention are discussed. Results Implementing the new diagnosis is currently challenged by a lack of well‐validated and reliable assessment measures, and observed continuities between SPCD and other neurodevelopmental disorders. High rates of comorbidity between SPCD and other seemingly disparate disorders (including conduct disorder, ADHD and disorders of known genetic origin) raise questions about the utility of this diagnostic category. Conclusions SPCD is probably best conceptualized as a dimensional symptom profile that may be present across a range of neurodevelopmental disorders, although there is an urgent need to investigate the latent structure of SPCD using consistent diagnostic criteria. In addition, social communication and aspects of pragmatic language may be dissociated, with the latter heavily influenced by structural language attainments. Finally, there is a dearth of reliable and culturally valid assessment measures with which to make a differential diagnosis, and few rigorously tested intervention programmes. The implications for research and clinical practice are outlined.